Studi Eksegetis 1Korintus 10: 1-5 Dan Kontribusinya Dalam Memahami Prinsip Baptisan Anak - Suleni Suleni (Sekolah Tinggi Teologi Arastamar Bengkulu, 2020)
Infant Baptism is a sacrament in the Chruch. But at this time many rejected the practice of infant baptism. The rejection comes from several Christian group. Many arguments have been given to assert the validity of Biblical infant baptism. However, these arguments have not yet been accepted by opponents of infant baptism. Through this article the author tries to contribute by 1Corinthians 10:1-5 as a basis for understanding infant baptism. This verse has not been widely exposed by Theologians to defend the argument about the validity of infant baptism. Thus, the reader can understand the true principle of infant baptism.